(untitled) (Higher Education Politics and Economics, 2020)
This two-way, fixed effects analysis examines the relationship between local appropriations and community college state governance structures while examining governance’s moderating impact on state-level factors. We find that any type of state-level organization for community colleges does not impact local appropriations, and that in states with no formal coordinating authority, local appropriations are likely to be higher. Further, the absence of a state-level board, even one that includes four-year, primary, or secondary education, moderates the relationship between unemployment and appropriations. This relationship suggests that in states without a state-level board for community colleges, local governments invest in and leverage their community colleges in times of economic decline.